Efeito da terapia fotodinâmica antimicrobiana na periodontite apical em modelo experimental de doença pulmonar obstrutiva crônica (DPOC) - Kamei, Sérgio Koiti (2020)
Introduction: Chronic obstructive pulmonary disease (COPD) is one of the main pulmonary diseases in the world population, affecting children, adolescents and adults, male and female. In the literature, there is a description of the interrelationship of systemic diseases such as cardiovascular and infectious periodontal diseases, the patients' plaque index and correlation between loss of periodontal insertion and decreased lung function, but there is no description in the literature. interrelation of respiratory diseases such as COPD and endodontic disease (asymptomatic apical periodontitis - PAA). Objective: To evaluate the effect of antimicrobial photodynamic therapy (aPDT) on asymptomatic apical periodontitis in an experimental model of chronic obstructive pulmonary disease (COPD), by counting macrophages, neutrophils and lymphocytes in lung BAL; quantify the levels of IL-1β, IL-4, IL-6, IL-10, INF-γ and TNF-α in BAL and serum and morphometrically analyze alveolar enlargement. Materials and Methods: Thus, both for the treatment of COPD and endodontic treatment, LASER is used in order to modulate inflammation and reduce infection. 64 mice were used, divided into 8 experimental groups: I-Basal (No disease induction), II- PAA (Asymptomatic apical periodontitis induction), III-PAA + TTO (PAA induction and endodontic treatment), IV-PAA + TTO + aPDT (PAA induction, endodontic treatment and antimicrobial photodynamic therapy), V-COPD (chronic obstructive pulmonary disease induction), VI-COPD + PAA (COPD induction, PAA), VII-COPD + PAA + TTO (induction of COPD, PAA and endodontic treatment), VIII-COPD + PAA + TTO + aPDT (COPD induction, PAA; endodontic treatment and antimicrobial photodynamic therapy). Results: In the total and differential count of inflammatory cells in the bronchoalveolar lavage there was an increase in the number of cells in the PAA and COPD groups. The number of macrophages was lower in the COPD + PAA group, which received endodontic treatment and photodynamic therapy as well. As for the number of lymphocytes, the COPD + PAA groups, after endodontic treatment and photodynamic therapy, showed a decrease in the number of cells. As for the number of neutrophils, the groups of diseases PAA and COPD, who received endodontic treatment associated or not with therapy, there was a decrease in the number of cells in relation to the respective PAA group. The cytokine IL-6 in serum and in BAL showed a reduction in relation to PAA and COPD diseases, except in the COPD + PAA + TTO group had a statistically equal number in the material removed from BAL. The amount of IL-10 in the serum decreased when PAA and COPD were associated. The results in the LBA showed that there was an increase in TNF-α in relation to the baseline group. And in the serum an increase in TNF-α in the association of COPD and PAA diseases submitted to endodontic treatment complemented by antimicrobial photodynamic therapy. Conclusion: Our data demonstrated that endodontic disease “per se” can cause pulmonary inflammation, without alveolar destruction in the lung. However, the association of COPD and PAA led to a reduction in pulmonary inflammation, thus being able to infer a protective effect on COPD. In addition, endodontic treatment associated or not with aPDT maintained this inhibitory effect of the pulmonary inflammatory response in an experimental model of COPD.